Short run and long run effects of corruption on economic growth: Evidence from Balkan countries - Stefano Lucarelli; Klodian Muço; Enzo Valentini (Economies, 2024)
One of the factors that characterize the different countries of the Balkan area is the level of corruption which, as often stressed by scholars, may significantly influence the economic growth of its countries. However, there is still no agreement on the sign of this effect: there are theoretical arguments and empirical results in favor of a positive correlation between corruption and growth, and there are also theoretical arguments and empirical results that support the opposite view. Comparing the short-term and long-term impacts can help to explain this contradiction. In this perspective, we propose an auto-regressive distributed lag (ARDL) methodology. This approach gives both short-run and long-run results simultaneously and it is robust with small samples. The results are not homogeneous for the eight countries covered by our study (Bulgaria, Croatia, Greece, North Macedonia, Romania, Serbia, Slovenia, and Turkey), but the following theoretical intuition is confirmed: although corruption could be seen as a factor that helps economic growth by speeding up the bureaucratic processing in the short run, conversely, in the long run, the social costs associated with corruption are considerable, making it difficult to sustain the political, economic, and social burdens, thus leading to a higher levels of corruption that negatively affect the economic growth. These results confirm certain aspects of Albert Hirschman's ideas regarding private interests and public action.
Keywords: 330; Albert Hirschman; Balkan countries; corruption; economic growth